Parenting young offenders: shaping and re-shaping social networks following custody 2016-2017 - McCarthy, Daniel (UK Data Service, 2019)
Data consists of qualitative interview data comprising a total of 31 transcripts. These consist of primary caregivers (majority mothers) related to young men (aged 15-22) in prison. Because of the sensitivity of this research, a number of transcripts have been omitted, including cases where interviewees did not want their data to be archived. Transcripts have been carefully anonymised, with any potentially identifiable details removed (especially details relating the nature of the offences committed). The project focuses on assessing the ways in which imprisonment creates wider impacts on family life, such as on parenting duties, physical and mental health of parents, as well as wider sources of social and economic disadvantage. As well as providing a comprehensive picture of the needs and experiences of parents, the research will be used to support and provide recommendations to the Prison Service, Youth Justice Service and Third Sector for creating more effective family-support policies and strategies, especially those which impact on resettlement and desistance where a number of gaps in policy and service provision have been identified (Prison Inspectorate, 2011, Youth Justice Board, 2012). This project will examine which networks prove barriers to parents, and which serve as facilitators and supporters in helping parents cope with the impact of having a child imprisoned. Here the research will conduct 60 in-depth interviews with parents of young men imprisoned, including those with community penalties or licenses attached to their sentence. The project focuses on assessing the ways in which imprisonment creates wider impacts on family life, such as on parenting duties, physical and mental health of parents, as well as wider sources of social and economic disadvantage. As well as providing a comprehensive picture of the needs and experiences of parents, the research will be used to support and provide recommendations to the Prison Service, Youth Justice Service and Third Sector for creating more effective family-support policies and strategies, especially those which impact on resettlement and desistance where a number of gaps in policy and service provision have been identified (Prison Inspectorate, 2011, Youth Justice Board, 2012).